Conditioned comfort: A multi-scalar analysis of residential heat adaptation in the tropical city-state of Singapore - Sarah Hian May Chan; Joshua Dao-Wei Sim; Natalia Borzino; Yunjing Li; Khant Min Naing; Pearl Min Sze Tan; Yi Xuan Tay; Flora Yuting Du; Samuel Chong Wei Chng; Jason Kai Wei Lee; Kai Zheng; Harvey Neo (Urban Climate, 2026)

First in situ observations of the goblin shark Mitsukurina owstoni - Aaron B. Judah; Alan J. Jamieson; Sarah R. D. Bingo; Megan E. Cundy; David A. Ebert; Steven Auscavitch; Harold K. Carlson; Tiffany Nicole G. Cunanan; Hayley B. Sims; Meagan Putts (Journal of Fish Biology, 2026)
We report the first live in situ observations of the iconic goblin shark ( Mitsukurina owstoni ) on a seamount near Jarvis Island in 2019 and on the slope of the Tonga Trench in 2024. Past observations are restricted to specimens hauled to the surface, resulting in limited knowledge of this species' ecology. These observations extend its known geographic and depth range considerably, and extend the depth range of lamniform sharks by 108 m. To further clarify habitat preferences and assess conservation status, further sampling, particularly with remote video, is required.

Enhancing the beneficial environmental impacts of seaweed cultivation: what do we understand about best practices? - Sophie J. I. Koch; Marcia Arredondo Rivera; Elisa Ciravegna; Julia Chatterton; Sarah Sim; Sander W. K. van den Burg (Journal of Applied Phycology, 2026)
Seaweed is increasingly discussed as a sustainable biomass source of the future, with applications in agricultural, food and cosmetics products and other areas of the biobased economy. The potential positive environmental impacts of seaweed cultivation have triggered public and private sector interest. This paper outlines the evidence for potential environmental benefits arising from seaweed cultivation focusing on climate change mitigation, biodiversity loss mitigation and improved water quality. Our findings are based on a descriptive literature review, coupled with insights and additional literature established during an expert review meeting. We found that seaweed cultivation can help to mitigate climate change and biodiversity loss and have beneficial impacts on water quality, but management practices may be key to maximizing these benefits and preventing negative environmental impacts. In particular, co-cultivating seaweed in integrated multi-trophic systems can enhance benefits. Other management practices expected to enhance environmental benefits of seaweed cultivation were identified, aligned to recently defined Principles of Restorative Aquaculture, including siting and structure used. Evidence of environmental impacts is often site-specific with considerable variability and uncertainty in the reported environmental benefits, due to the complexity of marine ecosystems and variability in cultivation and harvest practices. Systematic, long-term monitoring efforts are scarce, and more quantitative evidence is needed to support public and private sector decision-making for upscaling seaweed production in support of both bioeconomy and environmental restoration objectives. However, the management principles and practices identified in this paper can be used as interim guidance for decision-making.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Ensuring consistent data quality for environmental rating ecolabels with representative secondary datasets - Maëlys Courtat; P. James Joyce; Sarah Sim; Mohamad Kaddoura; Jhuma Sadhukhan; Richard Murphy (The International Journal of Life Cycle Assessment, 2025)
Purpose Environmental rating ecolabels (ERE) are developing rapidly across Europe, intending to guide sustainable purchasing choices through performance ratings derived from life cycle assessment (LCA). Integrating robust data quality methods in the LCA modelling stage is essential for accurate and comparable ratings, but challenging as ERE must be feasible to generate with reasonable effort for broad adoption. The use of secondary life cycle inventory (LCI) datasets, alongside actual product information such as bills of materials, is inevitable. However, the selection process for secondary LCI datasets and its implications for environmental ratings have yet to be investigated. Methods We examine the context-dependent suitability of secondary LCI datasets (aka their representativeness), hypothesising that differing levels of representativeness could lead to differences in product ratings. In a case study involving 94 laundry detergent products, we investigate how different secondary dataset choices influence the resulting aggregated LCA results (single scores), relative product rankings, and environmental ratings. Four distinct data scenarios are defined, in which the production of 19 key ingredients is represented through datasets of varying representativeness (from most specific to most generic). Results Over 60% of the products studied obtained a different rating under at least one of the three lower representativeness (more generic) data scenarios explored as compared with the rating obtained when the highest representativeness (most specific) data scenario was used. Lower representativeness scenarios also led to wider distributions of product single scores, with scenarios which utilised LCI data representing the function of ingredients (e.g. alkalinity source) or generic LCI data (e.g. organic chemicals) showing the most significant deviations from the distributions under the specific data scenario. This highlights the importance of having clearly defined, consistent data quality management approaches for the LCA stage of ERE. Conclusions Product information (e.g. formulation and packaging specifications) from primary sources should be combined with representative LCI datasets from third party databases to obtain reliable product ratings. We demonstrate that the representativeness of secondary datasets can be evaluated through three contextual indicators of data quality (technological, geographical, and temporal representativeness) to help guide the data selection process aligned to defined data quality thresholds. Based on our findings, practical recommendations are provided for data quality management in ERE. Scheme developers are encouraged to embed these in their methodologies to underpin transparent, robust labelling for product comparison.

Blue carbon management integrating socioeconomic and environmental interconnectivity in Southeast Asia: an urgent climate priority - Amani Becker; Sarah K. Bercovici; Jenny Choo; Fakhrurrozi Fakhrurrozi; Annabelle Fong; Sara E. Fowell; Emmy Hossain; Muhammad Ali Syed Hussein; Maryam Jamilah; Aazani Mujahid; Moritz Müller; Jillian Lean Sim Ooi; et al. (Frontiers in Marine Science, 2025)
This perspective article synthesises insights from a 2023 interdisciplinary workshop in Kuching, Malaysia, where 26 experts examined how land use and land cover change (LULCC) impacts Blue Carbon Ecosystems (BCE) in Southeast Asia (SEA) and identified pathways for integrated, science-informed governance. BCE in SEA (mangroves, seagrasses and tidal wetlands) are globally significant carbon sinks, critical to biodiversity and the livelihoods of millions, dependant on them for food, income and coastal protection. Yet rapid development and socio-economically driven LULCC threaten BCE resilience and carbon storage capacity. Blue Carbon initiatives risk falling short if they overlook the socio-ecological interconnectivity of these systems. Advances in remote sensing, sediment carbon accounting and ecosystem modelling have improved BCE monitoring, but key gaps persist. These include understanding cumulative upstream effects of LULCC on BCE carbon dynamics, integrating socio-economic with ecological data for robust scenario modelling and evaluating governance effectiveness and equity over time. We frame BCE as dynamic, interconnected socio-ecological systems and call for the advancement of systems thinking in coastal and climate policy. We underscore the need for transdisciplinary, nested governance models operating across ecological scales and political boundaries and argue for a systems-based management approach that links land-sea processes, addresses upstream-downstream dynamics and balances carbon market incentives with local needs. Recommendations include improved monitoring and carbon accounting; alignment between science and policy; regionally coordinated governance; and diversifying finance to reflect the full value of BCE beyond carbon. Together, these actions chart a path for resilient, science-based, socially inclusive BCE conservation in SEA.

Atherosclerotic Cardiovascular Disease in Gulf War Veterans in Relation to Deployment Exposures - Sarah T. Ahmed; Ruosha Li; Lea Steele; Peter Richardson; Kellie Sims; Rachel Quaden; Kelly M. Harrington; Vijay Nambi; John M. Gaziano; Robert Morgan; George L. Delclos; Drew A. Helmer (Cardiovascular Toxicology, 2025)
Many 1990–1991 Gulf War Veterans (GWVs) were exposed to toxicants and environmental hazards during deployment, including oil well fire smoke, chemical/biological agents, pyridostigmine bromide (PB) pills, and pesticides. Multiple constituents of smoke are associated with increased risk for atherosclerotic cardiovascular diseases (ASCVD), and other toxic exposures have been associated with autonomic and lipid dysfunction. We used data from the Gulf War Era Cohort and Biorepository Study of veterans deployed to Gulf War in 1990–1991 ( n = 942). We evaluated the association of deployment exposures (no, yes (1–6 days), (7–30 days), (31 + days), and not sure) with clinical risk factors (hypertension, diabetes, high cholesterol) and ASCVD using multivariable logistic regression. We adjusted for all clinical risk factors in the models to test the association of military exposures and ASCVD. We found that 7–30 days exposure to oil well fire smoke (OR: 2.95, CI: 1.40, 6.19), PB pills (OR: 2.37, CI: 1.06, 5.32), and chemical/biological agents (OR: 3.60, CI: 1.04, 12.51) were associated with ASCVD. Exposure to chemical/biological agents for 7–30 days was also associated with hypertension (OR: 4.18, CI: 1.48, 11.86) and for 31 + days was associated with ASCVD (OR: 4.24, CI:1.20, 14.94). The associations between oil well fire smoke and chemical/biological agents with ASCVD remained significant in models adjusting for clinical risk factors. For GWVs, exposure to oil well fire smoke, chemical/biological agents, and PB pills were associated with ASCVD. These exposures may represent population-specific risk enhancers for ASCVD and may be considered in individualized clinical risk assessment.

Environmental rating ecolabels: How does product categorization affect product ratings and potential interpretation? - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; David Sheffield; Richard Murphy (Journal of Industrial Ecology, 2025)
Environmental rating ecolabels (ERE) aim to present aggregated product environmental information to inform consumer choices. Performance ratings (e.g., A–E) are derived from life cycle assessment (LCA) results to enable comparison between products. The translation of LCA results to performance ratings requires definition of a common rating scale, either at a sector level or for subsets of products grouped by function (i.e., product categories). We investigate if and how assigning products to distinct categories influences final product ratings in ERE schemes. We consider if product categorization enables increased product differentiation and how the structure of categories affects the ratings awarded to products. Using a food sector case study, ratings were assigned to 2253 products based on aggregated environmental single scores derived from Agribalyse 3.1 and ratings obtained under three scenarios were compared: (1) no categorization—all products are placed on a single scale before rating; (2a) food group categorization—products are assigned to 11 food groups described in the Ciqual food composition database; and (2b) food subgroup categorization—products are assigned to 61 Ciqual food subgroups. We find that categorization has a significant influence on the final ratings, affecting at least 54% of products evaluated. Categorization restricts the range of products that can be compared but does not systematically improve differentiation within categories. For categorization to be used in ERE, categorization hierarchies need to be developed and harmonized at sector level reflecting consumer‐relevant substitution options. This study demonstrates that categorization is a key methodological consideration for ERE scheme developers.

Genomic infrastructure for cetacean research and conservation: reference genomes for eight families spanning the cetacean tree of life - Phillip A. Morin; Bernhard Bein; Chiara Bortoluzzi; Yury V. Bukhman; Taylor Hains; Dorothea Heimeier; Marcela Uliano-Silva; Dominic E. Absolon; Linelle Abueg; Jessica Antosiewicz-Bourget; Jennifer R. Balacco; Robert K. Bonde; et al. (Frontiers in Marine Science, 2025)
Reference genomes from representative species across families provide the critical infrastructure for research and conservation. The Cetacean Genomes Project (CGP) began in early 2020 to facilitate the generation of near error-free, chromosome-resolved reference genomes for all cetacean species. Towards that goal, and using the methods, goals and genome assembly quality standards of the Vertebrate Genomes Project (VGP), we generated 13 new reference genomes across eight of the 14 cetacean families. Additionally, we summarize the genome assembly characteristics for 18 species, including these newly-generated and five published genome assemblies that meet the completeness and quality standards. We infer ancestral linkage groups (ALG) for cetaceans, showing that the ancestral karyotype of 22 ALGs is largely conserved in extant species, except for Ziphiidae, and for Balaenidae and Kogiidae, which exhibit similar independent fusions. Gene annotation, characterization of historical demography, heterozygosity and runs of homozygosity (ROH) reveal important information for conservation applications. By comparing the new reference genomes to previous draft assemblies, we show that the reference genomes have enhanced characteristics that will support and promote scientific research. Specifically, the genomes improve resolution and characterization of repetitive elements, provide validation (or exclusion) of genes linked to complex traits, and allow more complete characterization of gene regions such as the highly complex Major Histocompatibility Complex (MHC) Class I and II gene clusters that are important for population health.

Multivariate Analysis of pH-Dependent Carbon Dots Sensitivity for Fe3⁺ Ions Detection Using UV–VIS Spectroscopy - Muna E. Raypah; Mohd Faizal Jamlos; Jelena Muncan; Ku Muhammad Naim Ku Khalif; Sarah Atifah Saruchi; Munira Mohd Ali; Chin Sim Yee; Agus Nugroho; Prabowo Puranto (Journal of Fluorescence, 2025)

Environmental rating ecolabels: Considerations for establishing a rating scale with categorical performance classes - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; Richard Murphy (Journal of Cleaner Production, 2025)

Prospective life cycle assessment of climate and biodiversity impacts of meat‐based and plant‐forward meals: A case study of Indonesian and German meal options - Sandra G. Marquardt; P. James Joyce; Giles Rigarlsford; Mariska Dötsch‐Klerk; Kathelijn van Elk; Jonathan Doelman; Vassilis Daioglou; Mark A. J. Huijbregts; Sarah Sim (Journal of Industrial Ecology, 2024)
The emerging field of prospective life cycle assessment (pLCA) offers opportunities for evaluating the environmental impacts of possible future consumption shifts. One such shift involves a transition from meat‐based to plant‐forward diets, acknowledged to mitigate environmental impacts of the food system under present day conditions. Current diets are often meat intensive (“meat‐based”), whilst “plant‐forward” diets include mainly plant‐based foods, encompassing flexitarian, vegetarian, and vegan diets. Here we illustrate the application of pLCA in a case study of meal options, implementing shared socio‐economic pathway scenarios in the LCA background system to represent future production conditions. We assess the climate footprints and land‐based biodiversity footprints of a typical meat‐based meal in Germany and Indonesia compared to a plant‐forward meal in both countries (i.e., four meals), now and in 2050. Our findings show that the plant‐forward alternative maintains a lower impact per serving in all future scenarios. At the same time, the reduction in impact for the meat‐based meals is more pronounced in future scenarios due to shifts in the agricultural system. Our findings highlight the importance of supply‐side measures to produce lower‐impact ingredients, complementing demand‐side interventions to reshape food consumption. Results are further evaluated in cultural and nutritional contexts, highlighting the practical decision‐making constraints faced by consumers. We find potential “leakage” effects in calories and nutrition when choosing a lower‐impact, plant‐forward meal. These leakage effects should be considered in future studies seeking to evaluate the environmental implications of meal substitutions in the context of broader dietary requirements.

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

The increasing importance of satellite observations to assess the ocean carbon sink and ocean acidification - Jamie D. Shutler; Nicolas Gruber; Helen S. Findlay; Peter E. Land; Luke Gregor; Thomas Holding; Richard P. Sims; Hannah Green; Jean-Francois Piolle; Bertrand Chapron; Shubha Sathyendranath; Cecile S. Rousseaux; et al. (Earth-Science Reviews, 2024)

Land use diversification may mitigate on‐site land use impacts on mammal populations and assemblages - Koen J. J. Kuipers; Sarah Sim; Jelle P. Hilbers; Stefanie K. van den Berg; Melinda M. J. de Jonge; Krista Trendafilova; Mark A. J. Huijbregts; Aafke M. Schipper (Global Change Biology, 2023)
Land use is a major cause of biodiversity decline worldwide. Agricultural and forestry diversification measures, such as the inclusion of natural elements or diversified crop types, may reduce impacts on biodiversity. However, the extent to which such measures may compensate for the negative impacts of land use remains unknown. To fill that gap, we synthesised data from 99 studies that recorded mammal populations or assemblages in natural reference sites and in cropland and forest plantations, with or without diversification measures. We quantified the responses to diversification measures based on individual species abundance, species richness and assemblage intactness as quantified by the mean species abundance indicator. In cropland with natural elements, mammal species abundance and richness were, on average, similar to natural conditions, while in cropland without natural elements they were reduced by 28% and 34%, respectively. We found that mammal species richness was comparable between diversified forest plantations and natural reference sites, and 32% lower in plantations without natural elements. In both cropland and plantations, assemblage intactness was reduced compared with natural reference conditions, but the reduction was smaller if diversification measures were in place. In addition, we found that responses to land use were modified by species traits and environmental context. While habitat specialist populations were reduced in cropland without diversification and in forest plantations, habitat generalists benefited. Furthermore, assemblages were impacted more by land use in tropical regions and landscapes containing a larger share of (semi)natural habitat compared with temperate regions and more converted landscapes. Given that mammal assemblage intactness is reduced also when diversification measures are in place, special attention should be directed to species that suffer from land use impacts. That said, our results suggest potential for reconciling land use and mammal conservation, provided that the diversification measures do not compromise yield.

Towards credible, evidence-based environmental rating ecolabels for consumer products: A proposed framework - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; Richard Murphy (Journal of Environmental Management, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Reimagining Policies, Practices, and Culture to Prevent and Respond to Sexual Assault and Sexual Harassment at NOAA - Emily Osborne; Catalina Martinez; Sim Aberson; Kristine Nelson; Sarah Duncan; Chassidy Ryals; Felix Muñoz; Thia Griffin-Elliott (Oceanography, 2023)
Sexual assault and sexual harassment (SASH) in STEM is a well-documented problem, particularly in academic and fieldwork settings (NASEM, 2018; Kelly and Yarincik, 2021; Ackerman et al., 2023). Historically marginalized groups in STEM (i.e., white women; Black, Indigenous, and other people of color; LGBTQ+ individuals) are particularly vulnerable to SASH due to underrepresentation and persistent, long-standing cultural norms shaped by dominant male and white identities. For individuals who hold multiple marginalized identities, the risks and impacts are compounded (Cech, 2022). SASH results in negative impacts to individual mental health and physical safety, productivity, and employee retention, and represents a barrier to entry, retention, advancement, and success of a diverse STEM workforce. To address this, culture change within STEM, the process of shifting organizational norms to promote improved employee wellness, inclusion, and productivity, is needed.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Corrigendum: On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)

On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)
Terrestrial runoff can negatively impact marine ecosystems through stressors including excess nutrients, freshwater, sediments, and contaminants. Severe storms, which are increasing with global climate change, generate massive inputs of runoff over short timescales (hours to days); such runoff impacted offshore reefs in the northwest Gulf of Mexico (NW GoM) following severe storms in 2016 and 2017. Several weeks after coastal flooding from these events, NW GoM reef corals, sponges, and other benthic invertebrates ∼185 km offshore experienced mortality (2016 only) and/or sub-lethal stress (both years). To assess the impact of storm-derived runoff on reef filter feeders, we characterized the bacterial communities of two sponges, Agelas clathrodes and Xestospongia muta , from offshore reefs during periods of sub-lethal stress and no stress over a three-year period (2016—2018). Sponge-associated and seawater-associated bacterial communities were altered during both flood years. Additionally, we found evidence of wastewater contamination (based on 16S rRNA gene libraries and quantitative PCR) in offshore sponge samples, but not in seawater samples, following these flood years. Signs of wastewater contamination were absent during the no-flood year. We show that flood events from severe storms have the capacity to reach offshore reef ecosystems and impact resident benthic organisms. Such impacts are most readily detected if baseline data on organismal physiology and associated microbiome composition are available. This highlights the need for molecular and microbial time series of benthic organisms in near- and offshore reef ecosystems, and the continued mitigation of stormwater runoff and climate change impacts.

Life cycle assessment applying planetary and regional boundaries to the process level: a model case study - Anders Bjørn; Sarah Sim; Henry King; Laure Patouillard; Manuele Margni; Michael Zwicky Hauschild; Morten Ryberg (The International Journal of Life Cycle Assessment, 2020)

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

Practical Approaches and Advances in Spatial Tools to Achieve Multi-Objective Marine Spatial Planning - Amanda T. Lombard; Natalie C. Ban; Joanna L. Smith; Sarah E. Lester; Kerry J. Sink; Spencer A. Wood; Aerin L. Jacob; Zacharoula Kyriazi; Richard Tingey; Helena E. Sims (Frontiers in Marine Science, 2019)

Tracking current and forecasting future land-use impacts of agricultural value chains. 67th Discussion Forum on Life Cycle Assessment, 3rd of November 2017, Zurich, Switzerland - Michal Kulak; Sarah Sim; Henry King; Wan Yee Lam; Sandra Marquardt; Mark Huijbregts (The International Journal of Life Cycle Assessment, 2018)

A test of the migration-modulation hypothesis in a non-passerine Neotropical migrant, the Blue-winged Teal Anas discors - C. Morgan Wilson; Christopher G. Sims; Stephan J. Schoech; Sarah K. Peltier; Zachary L. Robinson (Journal of Ornithology, 2017)

Species composition of coastal dune vegetation in Scotland has proved resistant to climate change over a third of a century - Robin J. Pakeman; Jim Alexander; Joan Beaton; Rob Brooker; Roger Cummins; Antonia Eastwood; Debbie Fielding; Julia Fisher; Sarah Gore; Richard Hewison; Russell Hooper; Jack Lennon; et al. (Global Change Biology, 2015)
Climate change is expected to have an impact on plant communities as increased temperatures are expected to drive individual species' distributions polewards. The results of a revisitation study after c. 34 years of 89 coastal sites in Scotland, UK, were examined to assess the degree of shifts in species composition that could be accounted for by climate change. There was little evidence for either species retreat northwards or for plots to become more dominated by species with a more southern distribution. At a few sites where significant change occurred, the changes were accounted for by the invasion, or in one instance the removal, of woody species. Also, the vegetation types that showed the most sensitivity to change were all early successional types and changes were primarily the result of succession rather than climate‐driven changes. Dune vegetation appears resistant to climate change impacts on the vegetation, either as the vegetation is inherently resistant to change, management prevents increased dominance of more southerly species or because of dispersal limitation to geographically isolated sites.

Land use impact assessment of margarine - Llorenç Milà i Canals; Giles Rigarlsford; Sarah Sim (The International Journal of Life Cycle Assessment, 2013)

Quantifying global greenhouse gas emissions from land‐use change for crop production - Helen C. Flynn; Llorenç Milà i. Canals; Emma Keller; Henry King; Sarah Sim; Astley Hastings; Shifeng Wang; Pete Smith (Global Change Biology, 2012)
Many assessments of product carbon footprint ( PCF ) for agricultural products omit emissions arising from land‐use change ( LUC ). In this study, we developed a framework based on IPCC national greenhouse gas inventory methodologies to assess the impacts of LUC from crop production using oil palm, soybean and oilseed rape as examples. Using ecological zone, climate and soil types from the top 20 producing countries, calculated emissions for transitions from natural vegetation to cropland on mineral soils under typical management ranged from −4.5 to 29.4 t CO 2 ‐eq ha −1 yr −1 over 20 years for oil palm and 1.2–47.5 t CO 2 ‐eq ha −1 yr −1 over 20 years for soybeans. Oilseed rape showed similar results to soybeans, but with lower maximum values because it is mainly grown in areas with lower C stocks. GHG emissions from other land‐use transitions were between 62% and 95% lower than those from natural vegetation for the arable crops, while conversions to oil palm were a sink for C . LUC emissions were considered on a national basis and also expressed per‐tonne‐of‐oil‐produced. Weighted global averages indicate that, depending on the land‐use transition, oil crop production on newly converted land contributes between −3.1 and 7.0 t CO 2 ‐eq t oil production −1 yr −1 for palm oil, 11.9–50.6 t CO 2 ‐eq t oil production −1 yr −1 for soybean oil, and 7.7–31.4 t CO 2 ‐eq t oil production −1 yr −1 for rapeseed oil. Assumptions made about crop and LUC distribution within countries contributed up to 66% error around the global averages for natural vegetation conversions. Uncertainty around biomass and soil C stocks were also examined. Finer resolution data and information (particularly on land management and yield) could improve reliability of the estimates but the framework can be used in all global regions and represents an important step forward for including LUC emissions in PCF s.

Estimating the greenhouse gas footprint of Knorr - Llorenç Milà i Canals; Sarah Sim; Tirma García-Suárez; Gabriele Neuer; Kathrin Herstein; Colin Kerr; Giles Rigarlsford; Henry King (The International Journal of Life Cycle Assessment, 2011)

Linkage disequilibrium between the CYP2C19*17 allele and wildtype CYP2C8 and CYP2C9 alleles: identification of CYP2C haplotypes in healthy Nordic populations - Rasmus S. Pedersen; Charlotte Brasch-Andersen; Sarah C. Sim; Troels K. Bergmann; Jónrit Halling; Maria S. Petersen; Pál Weihe; Hege Edvardsen; Vessela N. Kristensen; Kim Brøsen; Magnus Ingelman-Sundberg (European Journal of Clinical Pharmacology, 2010)

Comparative life cycle assessment of margarine and butter consumed in the UK, Germany and France - Katarina Nilsson; Anna Flysjö; Jennifer Davis; Sarah Sim; Nicole Unger; Simon Bell (The International Journal of Life Cycle Assessment, 2010)

MEXALCA: a modular method for the extrapolation of crop LCA - Anne Roches; Thomas Nemecek; Gérard Gaillard; Katharina Plassmann; Sarah Sim; Henry King; Llorenç Milà i Canals (The International Journal of Life Cycle Assessment, 2010)

Molecular genetics and epigenetics of the cytochrome P450 gene family and its relevance for cancer risk and treatment - Cristina Rodriguez-Antona; Alvin Gomez; Maria Karlgren; Sarah C. Sim; Magnus Ingelman-Sundberg (Human Genetics, 2010)

Kinetics of omeprazole and escitalopram in relation to the CYP2C19*17 allele in healthy subjects - Staffan Ohlsson Rosenborg; Jessica Mwinyi; Maria Andersson; R. Michael Baldwin; Rasmus Steen Pedersen; Sarah C. Sim; Leif Bertilsson; Magnus Ingelman-Sundberg; Erik Eliasson (European Journal of Clinical Pharmacology, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

The relative importance of transport in determining an appropriate sustainability strategy for food sourcing - Sarah Sim; Mike Barry; Roland Clift; Sarah J. Cowell (The International Journal of Life Cycle Assessment, 2007)

The relative importance of transport in determining an appropriate sustainability strategy for food sourcing - Sarah Sim; Mike Barry; Roland Clift; Sarah J. Cowell (The International Journal of Life Cycle Assessment, 2007)

Comparing domestic versus imported apples: A focus on energy use - Llorenç Milà i Canals; Sarah J. Cowell; Sarah Sim; Lauren Basson (Environmental Science and Pollution Research, 2007)

Identification of a single killer immunoglobulin-like receptor (KIR) gene in the porcine leukocyte receptor complex on chromosome 6q - Jennifer G. Sambrook; Harminder Sehra; Penny Coggill; Sean Humphray; Sophie Palmer; Sarah Sims; Haru-Hisa Takamatsu; Thomas Wileman; Alan L. Archibald; Stephan Beck (Immunogenetics, 2006)

Erratum - Sopheak K. Sim; Sarah M. Ohmann; Cindy B. S. Tong (American Journal of Potato Research, 1997)

Comparison of polyphenol oxidase in tubers ofSolanum tuberosum and the non-browning tubers ofS. hjertingii - Sopheak K. Sim; Sarah M. Ohmann; Cindy B. S. Tong (American Journal of Potato Research, 1997)